Conductometric Studies of Thermodynamics of 1,10-Didecyl-1,10-diaza-18-crown-6 Complexes with , , , , , , and Ions in Acetonitrile, Methanol, and Ethanol Solutions - Mehdi Taghdiri; Mahmood Payehghadr; Reza Behjatmanesh-Ardakani; Sirous Movahhedi; Farzaneh Nourifard (Journal of Chemistry)
The complexation reactions between 1,10-didecyl-1,10-diaza-18-crown-6 (DD18C6) and , , , , , and ions were studied conductometrically in acetonitrile, methanol, and ethanol at various temperatures. The formation constants of the resulting 1 : 1 complexes were calculated from the computer fitting of the molar conductance-mole ratio data at different temperatures. In the solvents studied, the stability of the resulting complexes varied in the order acetonitrile ≫ methanol > ethanol. The enthalpy and entropy changes of the complexation reactions were evaluated from the temperature dependence of formation constants. The versus plot of thermodynamic data obtained shows a linear correlation indicating the existence of enthalpy-entropy compensation in the complexation reactions. The ab initio studies calculated at B3LYP/6-31G level of theory indicate that the binding energy of complexes decreases with increasing cation size in the gas phase. The experimental data obtained in the solvents show different trends so that the stability constant of Li+ and Mg2+ complexes is lower than other alkali and alkaline earth ions, respectively due to the solvation of these small ions in solution.